Entrepreneurial Competence and Entrepreneur Profile for MSME Empowerment Program in Sukoharjo Regency - Wijanarko, Agung; Suryono, Joko (CV. BImbingan Belajar Assyfa, 2024)
In the information age, most MSMEs in Sukoharjo Regency face increasingly competitive business conditions. Information disclosure is both an opportunity and a challenge for the sustainability of their businesses. Many of their businesses are still in the pilot stage, and only a few can upgrade. This is because there are still many obstacles faced by entrepreneurs, such as (1) a weak understanding of business vision and mission planning, (2) a weak understanding of measuring the achievement of goals and objectives, (3) a weak understanding of the importance of self-capacity building and sustainable business development strategies. This empowerment is carried out by providing practical knowledge and strengthening entrepreneurial competencies. The empowerment outcomes are as follows: (1) strengthening understanding of business vision and mission planning, (2) strengthening understanding and ability to set and measure the achievement of business goals and objectives, (3) strengthening self-competence and guiding participants to design a blueprint for sustainable business strategies.